DOP41 Efficacy and safety of open-label treatment with tofacitinib 10 mg twice daily in patients with ulcerative colitis with clinical response, but not remission, after 52 weeks of maintenance therapy: data from the OCTAVE studies. (25th January 2019) - Chiorean, M; Su, C; Matsuoka, K; Orlando, A; Thorpe, A J; Nduaka, C I; Chapman, D S; Woodworth, D A; Lawendy, N; Friedman, G S; Cohen, R D
Abstract: Background: Tofacitinib is an oral, small-molecule JAK inhibitor approved in several countries for the treatment of ulcerative colitis (UC). We evaluated efficacy and safety of tofacitinib in patients with clinical response, but not remission, after 52 weeks of maintenance therapy in the OCTAVE Sustain study, who subsequently received tofacitinib 10 mg twice daily (BID) in an ongoing, open-label, long-term extension (OLE) study (OCTAVE Open; data as of November 2017). 1 Methods: We evaluated clinical response, remission, and mucosal healing based on Mayo score (using local endoscopic reading and non-responder imputation) in patients with clinical response but not remission (based on central endoscopic reading at Week 52 of OCTAVE Sustain) who received tofacitinib 10 mg BID in the OLE study. Efficacy is reported at Month (M) 2, M12, and M24 of the OLE by subgroups of prior tumour necrosis factor inhibitor (TNFi) failure (yes/no). Safety was assessed throughout the study. Results: Eighty patients were included in the analysis (18 received placebo in OCTAVE Sustain; 28 received tofacitinib 5 mg BID; 35 received 10 mg BID; 1 patient was randomised into OCTAVE Sustain in error and received 10 mg BID in the OLE). Thirty-eight of 82 (46.3%) had prior TNFi failure per induction baseline. Clinical response at M24 was maintained by 69.5% (41/59), 65.4% (17/26), and 72.7% (24/33) of patients overall, and with and without prior TNFi failure, respectively. By M2, the proportion of patients who had improved to remission, overall and for patients with and without prior TNFi failure, was 58.5% (48/82), 60.5% (23/38), and 56.8% (25/44), respectively. M2 remission rates were 77.8% (14/18) for patients who had received placebo in OCTAVE Sustain, 57.1% (16/28) for patients who had received 5 mg BID, and 50.0% (18/36) for patients who had received 10 mg BID (Figure 1). A summary of safety in the OLE clinical responder subpopulation is presented (Table 1). Conclusions: Over 50% of patients with UC who completed OCTAVE Sustain as clinical responders improved to remission within 2 months of receiving 10 mg BID in the OLE study. Efficacy was observed regardless of prior TNFi failure status. No new safety concerns associated with tofacitinib emerged with regard to the overall study population. 1 Reference 1. Lichtenstein GR. Tofacitinib, an oral Janus kinase inhibitor, in the treatment of ulcerative colitis: open-label, long-term extension study. Am J Gastroenterol 2017;112(S1): Abstract 714.